2017
DOI: 10.7566/jpsj.86.074709
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Insulator State of the Extended Falicov–Kimball Model in the Cluster Dynamical Impurity Approximation

Abstract: We comparatively study the excitonic insulator state in the extended Falicov-Kimball model (EFKM, a spinless two-band model) on the two-dimensional square lattice using the variational cluster approximation (VCA) and the cluster dynamical impurity approximation (CDIA). In the latter, the particle-bath sites are included in the reference cluster to take into account the particle-number fluctuations in the correlation sites. We thus calculate the particle-number distribution, order parameter, ground-state phase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…12,13) Several theoretical studies [14][15][16][17][18] have revealed that the transition is well accounted for by the excitonic condensation from a normal semiconductor (orthorhombic) to the EI (monoclinic) from a mean-field analysis for the 1-D threechain Hubbard model with electron-lattice coupling 14,16) and from a variational cluster approximation for the extended Falicov-Kimball model. 15,19) Recent optical measurements are also consistent with the EI phase below T c . 20,21) When the pressure is applied for Ta 2 NiSe 5 , 22,23) the structural phase transition temperature T c is suppressed and the system changes from semiconducting to semimetallic both above and below T c , and then, T c finally becomes zero at a critical pressure P c ∼ 8GPa, around which the superconductivity is observed.…”
Section: Introductionmentioning
confidence: 64%
“…12,13) Several theoretical studies [14][15][16][17][18] have revealed that the transition is well accounted for by the excitonic condensation from a normal semiconductor (orthorhombic) to the EI (monoclinic) from a mean-field analysis for the 1-D threechain Hubbard model with electron-lattice coupling 14,16) and from a variational cluster approximation for the extended Falicov-Kimball model. 15,19) Recent optical measurements are also consistent with the EI phase below T c . 20,21) When the pressure is applied for Ta 2 NiSe 5 , 22,23) the structural phase transition temperature T c is suppressed and the system changes from semiconducting to semimetallic both above and below T c , and then, T c finally becomes zero at a critical pressure P c ∼ 8GPa, around which the superconductivity is observed.…”
Section: Introductionmentioning
confidence: 64%
“…Some studies on the subject have also been performed for the extended version of the FKM (EFKM); e.g., Refs. [51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of Coulomb's interactions between electrons located on neighboring lattice sites have already been intensively investigated for the extended Hubbard model, e.g., Refs. [35][36][37][38][39][40][41][42][43][44] and references therein, while for the EFKM only very few results have been reported so far [34,[45][46][47][48][49]. As far as we know, exact results for the EFKM were only reported in Refs.…”
Section: Introductionmentioning
confidence: 99%